From Unsuccessful Attempts by Non Medical Personal to Surgery in Removing Rectal Foreign Bodies: Case Report - Yildiz, Mustafa; Mutlu, Bengu; Bozdemir, Mehmet Nuri; Gul, Evrim; Gurger, Mehtap; Alatas, Omer Dogan; Girgin, Mustafa (Emergency Medicine Physicians Assoc Turkey, 2013)
Intentional or unintentional insertion of foreign objects into the anus and rectum is a well-described phenomenon. A 40 year old man and 35 year old man presented to the emergency department after insertion of a high pressure container of tanning spray and insertion of a soda pop bottle into their rectum respectively. After an unsuccessful attempt to extract the foreign body at home, one patient tried to remove the foreign body by a piece of string which also stayed in the rectum. The foreign body was grasped with clamps and gently extracted in one case. In the other case, the foreign bodies were removed after sphincterotomy. To the best of our knowledge this is first case involving an attempt to remove the foreign body by a piece of string. We consider that removing a foreign body using string may involve a high risk of perforation, haemorrhage and infection. We describe two cases who presented at the emergency department with a rectal foreign body.
Keywords: Foreign body; rectum; string